Effect of Inhalational Anesthetics Exposure on Reproductive Outcomes and Its Predictors Among Healthcare Personnel in Jimma Zone Public Hospitals: A Comparative Cross-Sectional Study - Olika MK; Dessalegn ZM; Mekonin GT; Aboye MB; Wedajo MB; Ilala TT; Abebe DM; Demissie WR (Dove Medical Press, 2022)
Megersa Kelbesa Olika,1 Zemenu Muluken Dessalegn,1 Gezahegn Tesfaye Mekonin,1 Melka Biratu Aboye,1 Mitiku Berhanu Wedajo,1 Tajera Tageza Ilala,2 Dabessa Mosissa Abebe,3 Wondu Reta Demissie4 1Department of Anesthesia, Institute of Health, Jimma University, Jimma, Ethiopia; 2Department of Anesthesia, College of Medicine and Health Science, Hawassa University, Hawassa, Ethiopia; 3Department of Surgery, Institute of Health, Jimma University, Jimma, Ethiopia; 4Department of Biomedical Sciences, Institute of Health, Jimma University, Jimma, EthiopiaCorrespondence: Megersa Kelbesa Olika, Department of Anesthesia, Institute of Health, Jimma University, Jimma, Ethiopia, Tel +0912702005, Email megersakelbesa@gmail.comBackground: Emerging of anesthetics opens a new era to medical discipline in relieving patients' pain and stress when undergoing surgery but simultaneously exposes the healthcare personnel working in areas of anesthetics exposure to many adverse health effects including reproductive outcomes effects. Thus, this study aimed to assess the effect of inhalational anesthetics exposure on reproductive outcomes and its predictors among health care personnel in hospitals of Jimma zone public hospitals.Methods: A comparative cross-sectional study was conducted from May 01 to 30, 2021. We approached 483 healthcare personnel in Jimma zone public hospitals to partake in this study. Of this number, we recruited 292 healthcare personnel, comprising 146 exposed healthcare personnel and 146 unexposed healthcare personnel. Structured questionnaires were used to assess the reproductive outcomes. Data were entered into EPI-data version 4.6.1 and exported to SPSS version 24 for analysis. Binary logistic regressions were carried out to identify associated factors with reproductive outcomes. Statistical significance was declared using a p value < 0.05.Results: The overall prevalence of bad reproductive outcome status was high (30.8%) and the prevalence was much higher among exposed HCPs (20.9%) when compared to unexposed HCPs (9.9%). Among a total of 292 HCPs the likelihood of occurred bad reproductive outcomes was higher among an exposed group (AOR=3.17, 95% CI: 1.40- 7.16) and those who smoke cigarettes (AOR=8.44, 95% CI: 1.93- 36.91). The occurrence rate of bad reproductive outcome was higher among 30- 45h/week exposure (AOR=11.94, 95% CI: 1.25- 24.95) if separately analyzed among exposed and age of couple above 41 years among unexposed (AOR=5.87, 95% CI: 1.56- 22.06) were significantly associated with bad reproductive outcomes.Conclusion: Prevalence of bad reproductive outcomes was higher among exposed HCPs. Hence, it requires attention to create awareness about the danger of anesthetics exposure in the study setting, suggesting the need to further minimize the exposure.Keywords: inhalational anesthetics, exposure, effects, reproductive outcome, Jimma, Ethiopia